The Influence of Corporate Governance, Profitability, and Capital Intensity on Tax Avoidance in Manufacturing Companies Listed on the Idx in the Time Frame 2021-2023 - Andri Witomo; Zahid Zidan Qiam Arrahman (Riviera Publishing, 2024)
Tax avoidance is a significant issue that can affect state revenues and fiscal fairness. Companies often use legal loopholes to reduce their tax liability, which while legal, is contrary to the primary purpose of tax laws. This study aims to find out and analyze corporate governance, profitability, and capital intensity affect tax avoidance in manufacturing companies in Indonesia. This study uses a quantitative approach with secondary data from the financial statements of manufacturing companies listed on the IDX. The independent variables in this study are corporate governance (audit quality and audit committee), profitability, and capital intensity, while the dependent variable is tax avoidance. Data analysis was carried out by normality, multicollinearity, heteroscedasticity, autocorrelation, and hypothesis test using the t-test and the F test. However, simultaneously, audit quality, audit committee, profitability, and capital intensity affect tax avoidance. The study implies that an increase in the number of audit committees and investment in fixed assets can reduce tax avoidance. These findings can be a reference for policymakers and corporate management in improving corporate governance to minimize tax avoidance practices.